Pulmonary Tumor Microembolism - Bennink, R.; Wijngaerden, E. Van; Roo, M. De; Mortelmans, L. (Nuklearmedizin - NuclearMedicine, 1998)
Pulmonary tumor embolism is an often missed antemortem diagnosis in patients with cancer and respiratory failure. Although rare, this complication is an important cause of additional morbidity. Referred for radionuclide pulmonary perfusion and ventilation scintigraphy, a typical pattern of multiple subsegmental peripheral defects on perfusion lung scanning without matching ventilation defects, suggesting a high probability for pulmonary thromboembolism, often leads to false conclusions.We present a case of bilateral multiple subsegmental mismatched defects in lung ventilation perfusion scintigraphy, where autopsy confirmed the diagnosis of pulmonary tumor embolism, secondary to an undifferentiated ductal type adenocarcinoma of the pancreas. Pulmonary tumor embolism is an entity to keep in mind in patients treated for carcinoma presenting with (sub) acute dyspnea.
Keywords: Lung radionuclide imaging; neoplasm circulating cells; carcinoma infiltrating duct pathology; pancreatic neoplasm’s pathology; lung neoplasm’s secondary